Produtividade e qualidade de sementes do trigo duplo propósito em consórcio com cornichão na região da fronteira oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2012)
Wheat (Triticum aestivum L.) dual purpose for having two ends, emerges as an economic alternative for farmers because it serves both for the production of grain as feed for animals. The consortium is a legume with an efficient strategy to introduce more cheaply, nitrogen system, where legumes fix fix this molecule and act as a source of nitrogen. The objective of this study was to evaluate the yield and seed quality after management cuts at different heights in the period of vegetative stage. The experiment was conducted in fifteen plots divided into three replications of five treatments in randomized blocks. The treatments were: Treatment 1 (T1) - without cut; Treatment 2 (T2) - a cut and 5 cm; Treatment 3 (T3) - a cut and 10 cm in height; Treatment 4 (T4) - two cuts and 5 cm if height; Treatment 5 (T5) - two cuts and 10 cm height residue. Regarding the components of yield treatments showed statistically by analysis of variance (p <0.05). For variable yield the highest yield was observed in the uncut treatment (T1 2201.60 kg ha-¹) and lowest in the treatment of two cuts to 5 cm (T4 273.06 kg ha-¹). Regarding quality components significant difference (p <0.05), for germination and the treatment of two cuts to 5 cm which obtained the highest result (T5 78.94%). To this effect, there was no significant difference between treatments. Thus, it was concluded that, according to productivity treatments two cuts are not recommended as crop management. Treatments with more cuts positively influence germination.
Keywords: Alternativa econômica; Manejo de cortes; Produção de grãos; Economic alternative; Cuts management; Production; Triticum aestivum L.; CNPQ::CIENCIAS AGRARIAS